The Relationship Between Prescription Copayments and Contraceptive Adherence in a New-user Cohort - Marshall, Cassondra (Med Care, 2018)
BACKGROUND: Contraceptive nonadherence is an important contributor to unintended pregnancy in the United States. While the elimination of patient cost sharing has been cited as means to improve contraceptive access, little is known about the relationship between cost sharing and ongoing adherence and continuation of chosen methods. The purpose of this study was to examine the relationship between copayment amount and adherence to pharmacy-dispensed contraception in young women. METHODS: We conducted a retrospective cohort study of 39,142 women ages 19–29 with a new prescription for the contraceptive pill, patch, or ring at Kaiser Permanente Northern California during 2011–2014. We examined 12-month nonadherence as measured by timely prescription refills and used multivariable Cox proportional hazards models to assess the association between copayment amount and the risk of nonadherence. RESULTS: Ninety-four percent of women used the pill, and 6% used the patch or ring. Forty percent of patients had no copayment and 25% had a copayment of ≥ $30. Nearly 75% of women were non-adherent during the study period. In 2013 and 2014, women with a copayment had a 9% increased risk of nonadherence (adjusted hazard ratio, 1.09; 95% confidence interval, 1.04, 1.14) compared with women with no copayment. CONCLUSIONS: Prescription copayments may serve as a barrier to adherence of pharmacy-dispensed contraception. Given recent changes to Affordable Care Act contraceptive coverage requirement, these findings can be used to support state-level and health system-level policies for no-cost contraception, and to determine the potential public health impact of this policy change.